2014
DOI: 10.1002/2013je004592
|View full text |Cite
|
Sign up to set email alerts
|

The global albedo of the Moon at 1064 nm from LOLA

Abstract: The Lunar Orbiter Laser Altimeter (LOLA) measures the backscattered energy of the returning altimetric laser pulse at its wavelength of 1064 nm, and these data are used to map the reflectivity of the Moon at zero-phase angle with a photometrically uniform data set. Global maps have been produced at 4 pixels per degree (about 8 km at the equator) and 2 km resolution within 20°latitude of each pole. The zero-phase geometry is insensitive to lunar topography, so these data enable characterization of subtle variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 59 publications
(112 reference statements)
2
95
0
Order By: Relevance
“…Results from LRO's Lunar Observing Laser Altimeter albedo (LOLA) were used to suggest deposits of surface water frost on the walls of Shackleton crater using 1064 nm albedo measurements (Smith et al, 2010;Zuber et al, 2012). Lucey et al (2014) found LOLA albedo differences that are consistent with an interpretation of water frost deposition in PSR vs. non-PSR and on pole-facing slopes (PFS) vs. equator-facing slopes (EFS). Ground truth evidence of the existence of hydrogenbearing materials within a south polar PSR was established by the NIR and ultra-violet (UV) detection of water and molecular hydrogen within the excavated plume made by the exhausted rocket motor of the Lunar CRater Observing and Sensing Satellite (LCROSS) as it impacted Cabeus crater (Colaprete et al, 2010;Hurley et al, 2012).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Results from LRO's Lunar Observing Laser Altimeter albedo (LOLA) were used to suggest deposits of surface water frost on the walls of Shackleton crater using 1064 nm albedo measurements (Smith et al, 2010;Zuber et al, 2012). Lucey et al (2014) found LOLA albedo differences that are consistent with an interpretation of water frost deposition in PSR vs. non-PSR and on pole-facing slopes (PFS) vs. equator-facing slopes (EFS). Ground truth evidence of the existence of hydrogenbearing materials within a south polar PSR was established by the NIR and ultra-violet (UV) detection of water and molecular hydrogen within the excavated plume made by the exhausted rocket motor of the Lunar CRater Observing and Sensing Satellite (LCROSS) as it impacted Cabeus crater (Colaprete et al, 2010;Hurley et al, 2012).…”
Section: Introductionmentioning
confidence: 88%
“…Another potential explanation for the epithermal contrasts is that EFS and PFS slopes are diurnally exposed to very different temperature distributions that may lead to asymmetric space weathering, optical maturity or mass wasting effects that could influence epithermal rates (Lucey et al, 2014;Lawrence et al, 2014). Such a geochemical or geophysical alteration of the regolith identified here specific to PFS, would then have to at least partially cause the relative suppression of epithermal flux on PFS and also be latitude dependent, and maximized at the poles thus emulating the effects of locally enhanced hydrogen concentrations towards PFS.…”
Section: Slope Hydration Detection and The Dependence On Spatial Scalementioning
confidence: 99%
“…Recent measurements using neutron spectroscopy [Feldman et al 1998[Feldman et al , 2001Lawrence et al, 2006;Elphic et al, 2007;Mitrofanov et al, 2010], nearinfrared reflectance spectroscopy [Pieters et al 2009], thermal infrared radiometry [Paige et al 2010], far UV imaging and spectroscopy Hayne et al, 2015], and LIDAR reflectance [Zuber et al 2012;Lucey et al 2014], and in situ measurements [Colaprete et al, 2010] all point to the presence of water on the Moon. The Lunar Crater Observation and Sensing Satellite (LCROSS) impact into a permanently shadowed portion of Cabeus crater has provided the most direct evidence for the presence of water in the form of ice [Colaprete et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…This new understanding has resulted from multiple new types of measurements from orbital remote sensing and lunar sample analysis. Recent spacecraft observations and data analyses of the lunar poles have revealed new information about both the species, and spatial and depth-dependent distribution of volatiles within permanently shaded regions (Colaprete et al, 2010;Spudis et al, 2010;Miller et al, 2014;Lucey et al, 2014). Away from the poles, orbital spectral reflectance measurements have identified surficial enhancements of H 2 O/OH (Clark, 2009;Pieters et al, 2009;Sunshine et al, 2009;Klima et al, 2013).…”
Section: Introductionmentioning
confidence: 99%